TEKNOLOGI PRODUKSI NATA DE COCO BERBAHAN BAKU ORGANIK: Production Technology of Organic Nata De Coco - Lucia Cecilia Mandey; Dantje Tarore; Jenny E.A. Kandou; Natasia M. Dumais (Pro Food, 2020)
ABSTRACT Production research technology of nata de coco organic aims to find an alternative nitrogen source model to replace Urea Fertilizer (ZA) to produce quality nata de coco products and to implement this model in the community (UKM NATA de COCO). The benefit of this research is to produce quality nata de coco products and contain a source of fiber (dietary fiber). The quantitative Research Methods (laboratory experiments), with Phase I research carried out trough laboratory test with Treatment A = 10 liters of coconut water + 50 ml of bean sprouts extract; Treatment B = 10 liters of coconut water + 50 ml mung bean extract; Treatment C = basic ingredients of coconut water 10 liters + coconut milk 50 ml and Treatment D = basic ingredients of coconut water 10 liters + ZA Food Grade 20 grams + the palm tree sap and treatment E = basic ingredients of coconut water + ZA Non FOod Grade (control). The quality parameters of nata de coco studied were water content, rendemen, crude fiber content, thickness, color and weight of the pellicle. Next Phase II Research: Implementation of Alternative Nitrogen Substituted Urea Fertilizer (ZA) source models in Natural Cellulose Small Business (nata de Coco) in Airmadidi District, North Minahasa Regency. The results of the research: (1). Nitrogen sources are obtained from natural / organic ingredients such as: bean sprouts extract, green bean extract, coconut milk, as an alternative to Urea (ZA) fertilizer which can be used by bacteria Acetobacter xylinum to form natural cellulose pellicles, and a source of Acetobacter xylinum from the sap of the Enau tree. (2). A quality nata de coco product is obtained by providing a model for the use of “Food Grade” N sources in small businesses that produce nata de coco in Airmadidi District, North Minahasa Regency. Keywords: dietary fiber, nata de coco, organic ABSTRAK Penelitian Teknologi Produksi Nata De Coco Berbahan Baku Organik bertujuan untuk mendapatkan model sumber nitrogen alternatif pengganti Pupuk Urea (ZA) guna menghasilkan produk nata de coco yang berkualitas serta dapat mengimplementasikan model ini kepada masyarakat (UKM Nata de Coco). Manfaat penelitian ini guna menghasilkan produk nata de coco yang berkualitas dan mengandung sumber serat (dietary fiber). Metode Penelitian secara kuantitatif (eksperimen laboratorium), dengan Penelitian Tahap I dilakukan melalui uji laboratorium dengan Perlakuan A = bahan dasar air kelapa 10 liter + ekstrak tauge 50 ml; Perlakuan B = bahan dasar air kelapa 10 liter + ekstrak kacang hijau 50 ml; Perlakuan C = bahan dasar air kelapa 10 liter + santan kelapa 50 ml dan Perlakuan D = bahan dasar air kelapa 10 liter + ZA Food Grade 20 Gram + Nira Pohon Enau dan Perlakuan E = bahan dasar air kelapa + ZA Non Food Grade (Kontrol).Parameter kualitas nata de coco yang diteliti yaitu: kadar air, rendeman, kadar serat kasar, ketebalan, warna dan berat pelikel. Selanjutnya Penelitian Tahap II: Implementasi model sumber nitrogen alternatif pengganti Pupuk Urea (ZA) pada Usaha Kecil nata de coco di Kecamatan Airmadidi Kabupaten Minahasa Utara. Hasil penelitian yang dihasilkan: (1). Diperoleh Sumber Nitrogen dari bahan alami/organik seperti : ekstrak tauge, ekstrak kacang hijau, santan kelapa, sebagai alternatif pengganti Pupuk Urea (ZA) yang dapat digunakan oleh bakteri Acetobacter xylinum dalam menmbentuk pelikel selulosa alami, dan sumber Acetobacter xylinum dari nira pohon Enau. (2). Diperoleh produk nata de coco yang berkualitas dengan memberikan model penggunaan sumber N “Food Grade” pada Usaha Kecil yang memproduksi nata de coco di Kecamatan Airmadidi Kabupaten Minahasa Utara. Kata kunci: dietary fiber, nata de coco, organik